Analisis Kemiripan Visual Karakter Wajah Manusia Dalam Perancangan Desain Karakter Wajah 3D “Cerminan Bersaudara” - Putri, Ratih Alifah; Wahyudi, Luqman (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2023)
This study proposes an in-depth analysis approach to the visual resemblance of human facial characters within the context of designing 3D facial characters titled "Sibling Reflection." The analysis method employed involves a visual comparison approach, identifying and analyzing anatomical features and expressions of human facial characters. Principles of facial proportions, eye shapes, noses, mouths, and other anatomical details are explored to establish a reference foundation for the design of 3D facial characters. Guided by the data from the analysis of human facial characters, the subsequent step involves the design of the 3D facial character " Cerminan Bersaudara " using Blender software, with the goal of achieving a high level of visual resemblance. This design process encompasses iterative iterations, in-depth evaluations, and adjustments by design experts and animators. Through the proposed approach, this research aims to generate a 3D facial character design that approaches the level of visual resemblance achieved by Artificial Intelligence (AI) technology. The successful achievement of the expected visual resemblance in the design of the 3D facial character " Cerminan Bersaudara " is expected to have a positive impact on the audience's experience, particularly in the consumption of 3D character-based entertainment content